Treatment of early rheumatoid arthritis in a multinational inception cohort of Latin American patients: The GLADAR experience (2012)
Background Treatment of rheumatoid arthritis (RA) has evolved dramatically in the last decade. However, little is known about the way rheumatologists in Latin America treat their patients in clinical practice, outside the scope of clinical trials. Objective The objective of this study was to describe treatment patterns at disease onset in early RA with data from a large, multicenter, multinational inception cohort of Latin American patients. Methods Consecutive patients with early RA (<1 year of disease duration as diagnosed by a rheumatologist) from 46 centers in 14 Latin American countries were enrolled in the study. Clinical data, laboratory assessments, and a detailed registry on type of prescriptions were collected at baseline and at 3, 6, 12, 18, and 24 months of follow-up. Hands and feet x-rays were obtained at baseline and at 12 and 24 months. All data were captured in Arthros 6.1 database. Continuous variables were expressed as means and SDs, and categorical variables were expressed as percentages and 95% confidence intervals (95% CIs). Only therapeutic data at baseline are presented, corresponding to the period between disease onset and second visit (3 months). Results A total of 1093 patients were included. Eighty-five percent were female, and 76% had a positive rheumatoid factor. Mean age at diagnosis was 46.5 (SD, 14.2) years, and mean disease duration at the first visit was 5.8 (SD, 3.8) months. Between baseline and second visit (3 months), 75% of patients (95% CI, 72%–78%) received disease-modifying antirheumatic drugs. Methotrexate (MTX) alone or in combination was the most frequently used (60.5%), followed by antimalarials (chloroquine or hydroxychloroquine, 32.1%), sulfasalazine (7.1%), and leflunomide (LEF, 4%). In 474 patients (43%), initiation of disease-modifying antirheumatic drugs was within the first month after the first visit. In addition, 290 patients (26%; 95% CI, 23%–29%) received combination therapy as initial treatment. The most frequently used combinations were MTX + chloroquine (45%), MTX + hydroxychloroquine (25%), and MTX + sulfasalazine (16%). Eleven patients (1%; 95% CI, 0.5%–1.8%) received biologics. Sixty-four percent (95% CI, 60%–66%) received corticosteroids. Of those, 80% (95% CI, 77%–84%) received 10 mg of oral prednisone or less. Conclusions In this cohort of Latin American patients with early RA, most patients received MTX very early in their disease course. Combination therapy was used approximately in 1 of every 4 patients as initial therapy. Biologics were rarely used at this early stage, and low-dose prednisone was commonly used.